A Comprehensive Review on The Emerging Technologies in The Field of Robotics and Automation - Nitin K Kamble (AG Volumes, 2022)
Robotic automation is a continuously evolving field. Industrial robots have become prevalent in production settings throughout the globe in only a few decades, and their productivity as well as profitability continue to grow. Looking into the future is often difficult, but one thing is certain: robots will be a vital part of the future, accessing sections of the economy that people could only conceive a few years ago. Learning robots are becoming more common as artificial intelligence for the robotics matures. Here are six developing trends in the field of industrial robots which will most likely have a significant impact on a broad range of industrial industries and deliver advantages much beyond what was previously thought conceivable.